1999
DOI: 10.1136/bmj.318.7182.502
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic gastro-oesophageal reflux disease: double blind controlled study of intermittent treatment with omeprazole or ranitidine

Abstract: Objective To assess intermittent treatment over 12 months in patients with symptomatic gastro-oesophageal reflux disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 17 publications
3
94
0
7
Order By: Relevance
“…This is primarily due to studies showing that most patients with symptomatic GERD (60%) are contented with on-demand or intermittent PPI therapy. 40 On-demand therapy is a self-managed therapeutic strategy in which PPI intake is completely symptom driven, but patients are instructed not to take more than one PPI dose daily. 41 Studies have shown that 50% of the patients who consume PPI daily become on-demand takers within one month.…”
Section: On-demand/intermittent Therapymentioning
confidence: 99%
“…This is primarily due to studies showing that most patients with symptomatic GERD (60%) are contented with on-demand or intermittent PPI therapy. 40 On-demand therapy is a self-managed therapeutic strategy in which PPI intake is completely symptom driven, but patients are instructed not to take more than one PPI dose daily. 41 Studies have shown that 50% of the patients who consume PPI daily become on-demand takers within one month.…”
Section: On-demand/intermittent Therapymentioning
confidence: 99%
“…Comparison of gastrointestinal symptom rating scale (GSRS) total score, GSRS reflux score, GSRS abdominal pain score and Glasgow dyspepsia score as well as the psychological general well-being (PGWB) score during the course of the study and in those who had a successful PPI discontinuation Recent studies have shown that many GERD patients take PPIs on demand. 1,[19][20][21][22] In the current study, patients taking PPIs on demand were excluded. Most patients with GERD were willing to continue with PPIs on demand to control their symptoms but 50-60% of patients continued with placebo on demand.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is increasing support for the on-demand approach as the preferred strategy. [10][11][12] For example, Bardhan et al prospectively enrolled 526 patients and treated them with either an H 2 RA or proton pump inhibitor taken as needed. 10 Approximately 50% of the patients did not need to take any acid-suppressive medication for a minimum of 6 of the 12 months of the study.…”
Section: Choice Of Strategymentioning
confidence: 99%